PEDILAVIUM AS CONFLICT RECONCILIATION: EFFORTS TO INTERPRET THE BIBLICAL FOOT WASHING TRADITION AS RECONCILIATION OF INTERNAL CONFLICTS IN THE CHURCH - Ewen Josua Silitonga; Zulkarnain Siagian; Janhotner Saragih (Jurnal Scientia, 2023)
The rite of foot washing is a rite that has been practiced in the Bible for a long time, and has been known since the Old Testament. However, the meaning contained in it develops according to its context. If in the Old Testament washing feet shows a sense of courtesy and hospitality towards guests, then in the New Testament washing feet shows a moral example of humility and love. for that it is necessary to excavate contextually and relevantly the meaning of foot washing in the contemporary context. And seeing how Jesus used the rite of foot washing in reconciling the conflict that occurred between Himself and His disciples, in the tension of Judas' betrayal and the quarrel of the disciples who was the greatest among them? And how Jesus used foot washing, when Jesus experienced an internal conflict in himself before the suffering of His cross.